ANALISIS PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PENGAMBILAN SAHAM PERBANKAN BUMN YANG TERDAFTAR DI BEI PERIODE 2010-2014 - Sanuri Sanuri; Desta Rizky Kusuma (Jurnal Fokus Manajemen Bisnis, 2016)
This study aims to determine the influence of factors internal and external to the return of registered banking shares Indonesia Stock Exchange in 2010-2014. The population in this study were 4 BUMN bank companies registered in Indonesia Stock Exchange period 2010-2014 sampling techniques used is purposive sampling. obtained by 4 state-owned bank companies included in the independent variable criterion studied is Return On Assets (ROA), Capital Adequacy Ratio (CAR), Inflation Rate, and Rate of Interest Interest and the dependent variable studied is stock returns. Analysis Techniques used is Panel Data Regression and Hypothesis test using t-test. The results showed that both variables were simultaneously independent Return On Asset (ROA) has no effect on stock returns Partially the variables of the four independent variables are Return On Assets (ROA), Capital Adequacy Ratio (CAR), Inflation and Interest Rates are only Inflation and Interest rates that have a significant effect on stock returns. R-square value 33.42%.